Contractual conditions and major delays in a thermal power plant construction project : a case study of Vietnam - Nguyen Thi Huyen Trang; Hadikusumo, Bonaventura H. W.; Chotchai Charoenngam; Santi Charoenpornpattana; Vietnam Electricity (EVN) (Pathum Thani, Thailand : Asian Institute of Technology, 2018)
Rapid economic development in Vietnam in recent years has led to the increase in power demand. With a variety of energy sources such as coal, gas, oil etc., the power sector's structure of Vietnam has shifted from hydropower to thermal power. However, the delay of construction of thermal power plant has become a concerning problem to ensure energy security and stability for the country's economic development. Based on literature review from books, journal articles and other sources, construction delay is caused by many factors such as owner- related, contractor- related, consultant- related and external- related factors. As a result, this research is conducted to study one particular case of delay in thermal power plant project to identify root causes of delay during construction stage in comparison with theory, especially delays related with contract conditions and administration. Ten major delay problems of this case are analyzed carefully based on actual activities on site and related contractual conditions. Associated contract management of the owner and subsequent solutions to mitigate the problem are discussed in detail as well. From all the analysis, specific recommendations are given to each delay event to help owner avoid or minimize the effect of similar problem in the future. Moreover, general lessons learnt from the study case are given on how to select competent contractors, prepare good contract document and improve management skill of owner's management board to carry out future projects successfully on time.
A project submitted in partial fulfillment of the requirements for the degree of Master of Engineering (Professional) in Construction, Engineering and Infrastructure Management
Project (M. Eng.) - Asian Institute of Technology, 2018
Keywords: Electric power-plants -- Construction -- Vietnam; Construction contracts -- Vietnam -- Case studies